Immobilization of the Tannase From Aspergillus fumigatus CAS21: Screening the Best Derivative for the Treatment of Tannery Effluent Using a Packed Bed Reactor - Cavalcanti, Rayza Morganna Farias; Maestrello, Chadia Chahud; Guimarães, Luis Henrique Souza (Frontiers in Bioengineering and Biotechnology, 2021)
Enzyme immobilization is an important alternative to stabilize enzyme properties favoring the efficiency of derivatives (enzyme + support/matrix) for different purposes. According to this, the current study aimed to immobilize the Aspergillus fumigatus CAS21 tannase and the use of the derivatives in the treatment of the effluent produced by the tanning industry. The tannase was immobilized on sodium alginate, DEAE-Sephadex, amberlite and glass pearls as supports. Calcium alginate was the most adequate support for tannase immobilization with 100% yield and 94.3% for both efficiency and activity. The best tannase activity for the calcium alginate derivative was obtained at 50-60 ºC and pH 5.0. Thermal and pH stabilities evaluated for 24 h at 30-60 ºC and pH 4-7, respectively, were improved if compared to the stability of the free enzyme. Considering the reuse of the calcium alginate derivative, 78% of the initial activity was preserved after 10 catalytic cycles and after the 9-month storage at 4 ºC, the activity was maintained in 70%. This derivative was applied in a packed bed reactor (PBR) for the treatment of tannin-rich effluents from the tannery industry. The reduction of the tannin content was effective reaching degradation of 74-78% after 48 h of PBR operation. The concentration of total phenolic compounds was also reduced, and the color and clarity of the effluent improved. In conclusion, the calcium alginate derivative is an attractive alternative as biocatalyst for large-scale treatment of the effluents from the tannery industry.